1996
DOI: 10.1111/j.1365-2044.1996.tb12566.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for cardioversion

Abstract: SummaryCarcliocersion is a nzinor procedure requiring sedation and uiiulgesia. HobLwer, it is often pei;fornied out-of-hours

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 57 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Propofol has been used for procedural sedation in Emergency Medicine since 1995 7. In 1996, in a review article in Anaesthesia ,8 it was recommended as the drug which most closely approaches the ideal agent for cardioversion; however, a systematic review of the use of propofol for procedural sedation in Emergency Medicine in 2001 concluded that although there was evidence to support the use of propofol for DCCV this evidence came from stable patients in a non-ED setting, and there was as yet no evidence to support its use in emergency practice 9. Since then, Miner et al 10 have shown that procedural sedation in the ED with propofol appears to be safe in ASA class III and IV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been used for procedural sedation in Emergency Medicine since 1995 7. In 1996, in a review article in Anaesthesia ,8 it was recommended as the drug which most closely approaches the ideal agent for cardioversion; however, a systematic review of the use of propofol for procedural sedation in Emergency Medicine in 2001 concluded that although there was evidence to support the use of propofol for DCCV this evidence came from stable patients in a non-ED setting, and there was as yet no evidence to support its use in emergency practice 9. Since then, Miner et al 10 have shown that procedural sedation in the ED with propofol appears to be safe in ASA class III and IV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that patients' reactions may complicate CV procedures. 1,19,32 Payen et al evaluated patient reactions by using a Behavioral Pain Scale 33 and reported that the medication dosage can be adjusted by this scale. Ammer et al applied low-voltage intracardiac CV.…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting conditions such as previous myocardial infarction, congestive heart failure, angina, hypertension, chronic renal failure, chronic hepatic insufficiency, electrolyte imbalance, other concurrent medications, and the age of the patient have been considered in the selection of agents. [1][2][3][4][5][6][7][8][9][10] Midazolam and propofol frequently have been used for CV sedation. [11][12][13][14][15][16][17] However, different studies report different application techniques, doses, and side effects, [2][3][4][6][7][8]10,12,15,[18][19][20][21] and data on age-specific efficacy and side effects of midazolam and propofol when used in procedural sedation have been limited.…”
mentioning
confidence: 99%
“…Other anesthetic agents used for cardioversion include etomidate, sodium thiopental, and midazolam. 5,6 The success of cardioversion depends on the delivery of adequate current to the heart. Internal cardioversion is rarely used in clinical practice as it is an invasive procedure, and current external cardioversion techniques are successful in most patients.…”
Section: Electrical Cardioversionmentioning
confidence: 99%